Pengaruh Pembagian Tugas Dengan Efektivitas Kerja Kepala Kampung Jengan Danum di Kecamatan Damai Kabupaten Kutai Barat - Jovinus Juvenalis (Universitas 17 Agustus 1945 Samarinda, 2021)
The purpose of this study is to find out whether the division of duties has anything to do with the effectiveness of the work of the Head of Kampung Jengan Danum in the Peaceful District of West Kutai Regency. Therefore, the author obtained an overview of the division of duties and the effectiveness of employee work is very important so that employees better understand more deeply about the concept of State Administration in the context of task division to support the successful implementation of tasks well in the environment of the Head of Jengan Danum Village, West Kutai Regency Peace District. Although the division of tasks is not the only factor that supports success to create employee work effectiveness, it turns out that the task division factor is quite affecting the effectiveness of employee work. As the Leader it is recommended that more attention to the individual needs of its employees, as well as provide freedom for their employees to develop their creativity and provide a broader experience to employees through continuous development activities. And to the employees, especially those who were respondents in this study, it is recommended that they continue to improve morale and ability to bring the mission of the organization under the level of increasingly tight competition, so that it will be created well, which can simultaneously improve the performance of the organization in the face of global competition. The purpose of this study is to find out whether the division of duties has anything to do with the effectiveness of the work of the Head of Kampung Jengan Danum in the Peaceful District of West Kutai Regency. Therefore, the author obtained an overview of the division of duties and the effectiveness of employee work is very important so that employees better understand more deeply about the concept of State Administration in the context of task division to support the successful implementation of tasks well in the environment of the Head of Jengan Danum Village, West Kutai Regency Peace District. Although the division of tasks is not the only factor that supports success to create employee work effectiveness, it turns out that the task division factor is quite affecting the effectiveness of employee work. As the Leader it is recommended that more attention to the individual needs of its employees, as well as provide freedom for their employees to develop their creativity and provide a broader experience to employees through continuous development activities. And to the employees, especially those who were respondents in this study, it is recommended that they continue to improve morale and ability to bring the mission of the organization under the level of increasingly tight competition, so that it will be created well, which can simultaneously improve the performance of the organization in the face of global competition.